ChemInform Abstract: Nucleic Acid Aptamers: An Emerging Frontier in Cancer Therapy. Issue 3 (22nd January 2013) - Zhu, Guizhi; Ye, Mao; Donovan, Michael J.; Song, Erqun; Zhao, Zilong; Tan, Weihong
Abstract Review: 114 refs.